The IMB Working Paper No. 100: Taking stock and moving forward - Christoph Dörrenbächer; Marianne Egger de Campo; Matthias Tomenendal (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2021)
This is the 100th issue of the IMB Working Papers. It contains three short papers on the series itself. The first paper takes stock of the history, content and relevance of the IMB Working Paper Series. It analyses the first 100 issues of the series in detail (Dörrenbächer in this volume, pp. 4-15). The second paper is addressing the changes at the institution publishing the IMB Working Paper Series. Having been merged with an Institute for Long-Distance Studies, the IMB (Institute of Management Berlin) was re-named to BPS (Berlin Professional School), bringing professionalism to center stage (Tomenendal and Egger de Campo in this volume, pp.16-19). The third paper looks ahead and describes the future ambitions of the working paper series, which will appear as BPS Working Paper Series in the future. Aspects covered are the rationale, scope and way of delivery of the series (Dörrenbächer and Tomenendal in this issue, pp. 20-23). – – Dies ist die 100. Ausgabe der IMB Working Paper Reihe. Sie beinhaltet drei Kurzbeiträge, die sich mit der Reihe, ihrer Entwicklung und ihrer Zukunft auseinandersetzen. Der erste Beitrag analysiert in einer Rückschau die Inhalte und die Relevanz der bisher veröffentlichen Working Papers (Dörrenbächer, Seite 4-15). Der zweite Beitrag beschäftigt sich mit dem Wandel der herausgebenden Institution, die nach einer Fusion nun als Berlin Professional School für eine fundierte, praxisorientierte Managementausbildung für Wirtschaft und Verwaltung steht (Tomenendal and Egger de Campo, Seite 16-19). Der letzte Beitrag zeigt Zukunftsperspektiven für die ab der nächsten Nummer als BPS Working Papers Series firmierende Reihe auf. Neben zukünftigen inhaltlichen Schwerpunkten werden Vorschläge für eine erhöhte Sichtbarkeit und Zugänglichkeit der Reihe gemacht (Dörrenbächer und Tomenendal, Seite 20-23).
Keywords: 330